Isolation and Characterization of Thermophilic Bacillus subtilis subsp. inaquosorum CGR-1 from Cangar Hot Springs - Aulia Azzahra; Dimas Aryq Ijlal Wafi; Febriani Sukma Maghfirotul Chasanah; Lillah Asritafriha; Rizki Amaliah Zain; Us Watun Nurul Khasanah; Geraldi, Almando (Universitas Airlangga, 2022)
Bioindustries often involve biochemical processes that occur at higher temperatures. However, most proteins, including enzymes, lose their structural integrity and functionality at higher temperatures. Thus, thermostable enzymes from thermophilic microorganisms are best suited candidates for successful bioprocessing under such conditions. Indonesia is one of the best study sites for performing bioprospecting of thermostable enzyme-producing thermophilic microorganisms due to the numerous hot springs. To explore the biodiversity of thermophilic microorganisms with potential industrial applications, we isolated and characterized thermophilic bacteria from the Cangar hot spring, Batu, East Java, Indonesia. One isolate (CGR-1) showed growth at 60°C and was identified as Bacillus subtilis subsp. inaquosorum based on 16s rRNA gene sequencing followed by bioinformatic analysis. This is the first report on the isolation of Bacillus subtilis subsp. inaquosorum CGR-1 from Indonesia, especially from a hot spring environment. This isolate showed cellulolytic and amylolytic activity at 50°C, which would encourage further exploration on the industrial and environmental applications.